Non-Native English-Speaking Tutor: The Students’ Perception at English Education Center In Banyuwangi: Bukan Penutur Asli Bahasa Inggris Speaking Tutor: Persepsi Siswa di Pusat Pembelajaran Bahasa Inggris di Banyuwangi - Rizki Nurfida Pambayun; Dian Arief Pradana; Ifa Muhimmatin; Moch. Ardi Setyawan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research was examined to gain student’s perception of non-native English-Speaking Tutor: at English education centre in Banyuwangi. There were 28 students of Desy Education Banyuwangi as the participant of this research. The research instruments applied were questionnaire and interview. The data analyzed by using qualitative data analysis techniques such as flow model and tabulating data. Based on the whole instruments and techniques applied, the researcher found out 24 points which written clearly in the table as the final result of questionnaire. In addition, interview was used to support the answers of students’ questionnaire. The result shown that half of students (68%) stated that the skills and the success of non-native English-speaking tutors inspired them to achieve the same or even better competence than NNEST. Furthermore, the students' positive perceptions were also strengthened by the results of interviews which indicated that students gave positive perceptions which explained that if they were highly motivated and confident, they could achieve success in speaking like NNEST. So, it can be conclude that most of the students had the positive perception of Non-native English Speaking Tutor: at English Education Centre in Banyuwangi.